HRM and KM practices in ISTIQ: lessons to learn - Omar, Anuar; MohdAzlan, Azian; Kadir, Samila; Hazaipah, Siti Nur Hafiza; Mhd. Sarif, Suhaimi (Graduate School of Management IIUM, 2011)
This case study addresses issues of human resource management (HRM)and knowledge management (KM) practices at ISTIQ Sdn. Bhd. ISTIQ is a local company that has ventured into an interesting field - noise control engineering.ISTIQ began as an humble engineering company that discovered opportunities in noise control engineering and expanded to serve both regional and international markets. However, the employees of ISTIQ are neither vibrant and dynamic nor sufficiently proficient in responding to the requirements of their customers. Efforts to address these deficiency problems include on-the-job and off-the-job training programmes, technical workshops and English courses. A topping up measure was a recent review of its hiring practices to be in line with human resource and knowledge management requirements.